EFEKTIVITAS DISCOVERY LEARNING BERBASIS SCIENTIFIC PRACTICES DALAM MENINGKATKAN SCIENTIFIC THINKING PESERTA DIDIK - Eka Maulidiah, Sisilia; Arif Mahdiannur, Muhamad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the importance of strengthening scientific thinking skills as one of the 21st-century skills and is in line with the PISA 2025 framework that emphasizes competencies related to scientific inquiry. Therefore, this study integrates the discovery learning model with scientific practices to actively engage students in scientific inquiry activities and train scientific thinking skills. The study used a pre-experimental method with a one-group pre-test post-test design conducted in class VII-E at State Junior High School 46 Surabaya accompanied by paired t-test analysis and Cohen's d effect size. The results showed a significant difference between the pre-test and post-test scores. The results were strengthened by the effect size value of 3.209 with a very high category. All average post-test scores of scientific thinking indicators also showed an increase from the pre-test scores after the implementation of the discovery learning model based on scientific practices. The highest effect size value was found in the inquiry indicator, while the lowest was in the analysis indicator